LC-MS/MS assay for the determination of lurasidone and its active metabolite, ID-14283 in human plasma and its application to a clinical pharmacokinetic study - Katteboina, Mahitej Yadav; Pilli, Nageswara Rao; Mullangi, Ramesh; Seelam, Raghunadha Reddy; Satla, Shobha Rani (Biomedical chromatography, 2016)
The authors proposed a sensitive, selective and rapid liquid chromatography–tandem mass spectrometric (LC‐MS/MS) assay procedure for the quantification of lurasidone and its active metabolite, i.e. ID‐14283 in human plasma simultaneously using corresponding isotope labeled compounds as internal standards as per regulatory guidelines. After liquid–liquid extraction with tert‐butyl methyl ether, the analytes were chromatographed on a C18 column using an optimized mobile phase composed of 5 mm ammonium acetate (pH 5.0) and acetonitrile (15:85, v/v) and delivered at a flow rate of 1.00 mL/min. The assay exhibits excellent linearity in the concentration ranges of 0.25–100 and 0.10–14.1 ng/mL for lurasidone and ID‐14283, respectively. The precision and accuracy results over five concentration levels in four different batches were well within the acceptance limits. Lurasidone and ID‐14283 were found to be stable in battery of stability studies. The method was rapid with the chromatographic run time 2.5 min, which made it possible to analyze 300 samples in a single day. Additionally, this method was successfully used to estimate the in vivo plasma concentrations of lurasidone and ID‐14283 obtained from a pharmacokinetic study in south Indian male subjects and the results were authenticated by conducting incurred samples reanalysis. Copyright © 2015 John Wiley & Sons, Ltd.